6j=3+5j

Simple and best practice solution for 6j=3+5j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6j=3+5j equation:


Simplifying
6j = 3 + 5j

Solving
6j = 3 + 5j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-5j' to each side of the equation.
6j + -5j = 3 + 5j + -5j

Combine like terms: 6j + -5j = 1j
1j = 3 + 5j + -5j

Combine like terms: 5j + -5j = 0
1j = 3 + 0
1j = 3

Divide each side by '1'.
j = 3

Simplifying
j = 3

See similar equations:

| 12b=-12b | | 2h+9=3h | | (-2x+92)=(x+8) | | -5+4k=9k | | 4y-2(y+5)=0 | | 7v=-9+6v | | (4x+30)=(-2x+54) | | a-3=45 | | 10+4w=6w | | -5x+8x-4x=0 | | 9+9y=8y | | -5x+8x=0 | | -5p=-8+3p | | -[7x-(3x+4)]=-5-[4(2x-4)-2x] | | -21/-2 | | -3x+6x-7x=o | | y=7-(1/2)x | | 8/9*6/9 | | b=-21+-2d | | y^2-5x^2+50x+6y=141 | | -7x+5=-4x+27 | | SA=2(LW+lh+wh)forw | | Z+19=90 | | x-3t=yt | | 12h=9h | | -8x-6=50+3x | | 6t=-2 | | -8x-6=50 | | 2x-5=343 | | 6-3t=9t | | 5t=-2 | | 13x-(x+7)=12x-13 |

Equations solver categories